Rexinoids Modulate Effector T Cell Expression of Mucosal Homing Markers CCR9 and α4β7 Integrin and Direct Their Migration In Vitro - Manhas, Kavita R.; Marshall, Pamela A.; Wagner, Carl E.; Jurutka, Peter W.; Mancenido, Michelle V.; Debray, Hannah Z.; Blattman, Joseph N. (Frontiers in Immunology, 2022)
Altering T cell trafficking to mucosal regions can enhance immune responses towards pathogenic infections and cancers at these sites, leading to better outcomes. All-trans-retinoic acid (ATRA) promotes T cell migration to mucosal surfaces by inducing transcription of the mucosal-homing receptors CCR9 and a4b7 via binding to the retinoic acid receptor (RAR), which heterodimerizes with the retinoid X receptor (RXR) to function. However, the unstable nature and toxicity of ATRA limit its use as a widespread treatment modality for mucosal diseases. Therefore, identifying alternatives that could reduce or eliminate the use of ATRA are needed. Rexinoids are synthetically derived compounds structurally similar to ATRA. Originally named for their ability to bind the RXR, rexinoids can enhance RAR-mediated gene transcription. Furthermore, rexinoids are more stable than ATRA and possess an improved safety profile, making them attractive candidates for use in clinical settings. Here we show that select novel rexinoids act as ATRA mimics, as they cause increased CCR9 and a4b7 expression and enhanced migration to the CCR9 ligand, CCL25 in vitro, even in the absence of ATRA. Conversely, other rexinoids act synergistically with ATRA, as culturing cells with suboptimal doses of both compounds resulted in CCR9 expression and migration to CCL25. Overall, our findings show that rexinoids can be used independently or synergistically with ATRA to promote mucosal homing of T cells in vitro, and lends support for the prospective clinical use of these compounds in immunotherapeutic approaches for pathogenic infections or cancers at mucosal surfaces.